Unsteady Boundary Layer Separated Stagnation-Point Flow towards a Permeable Shrinking Sheet - Lok, Yian Yian; Ahmad , Syakila (AIP Publishing, 2014)
A study of the unsteady separated stagnation-point flow with constant suction towards a shrinking sheet is presented. A similarity transformation reduces the governing partial differential equation to the third order nonlinear ordinary differential equation which the terms of unsteady effect are clearly shown. The problem is solved numerically where the influences of shrinking and suction parameters on flow are studied. It is found that two solutions exist, one representing an attached flow while the other a reverse flow. It is found that adequate suction is necessary for the solutions to exist.